METHODOLOGY FOR USING UNTRADITIONAL ILLUSTRATIVE ACTIVITIES FOR PRESCHOOL CHILDREN 5-7 YEARS OLD - Aziza Yusupova (Web of Journals Publishing, 2024)
This article discusses the issues of expanding the role of non-traditional drawing classes in visual activity classes in preschool educational organizations, further enriching children 's creative thinking, revitalizing new perspectives on life, and expanding their opportunities to enjoy what they are doing, based on children's capabilities, filling them with variety based on innovative technologies, developing children's self-confidence, and teaching them creative skills in new directions using little fingers.
Keywords: Education, upbringing, improvement, movement, innovative ideas, innovative technologies, children's creativity, new world experiences, cooperation, issues of solidarity.